MPLS network management MIBs, tools, and techniques - Nadeau, Thomas D. (San Francisco, Calif. : Morgan Kaufmann, 2003)
MPLS-enabled networks are enjoying tremendous growth, but practical information on managing MPLS-enabled networks has remained hard to find. Until now. MPLS Network Management: MIBs, Tools, and Techniques is the first and only book that will help you master MPLS management technologies and techniques, as they apply to classic MPLS networks, traffic-engineered networks, and VPNs. Written by the co-author of most current MPLS management standards, it provides detailed, authoritative coverage of official MIBs, examining key topics ranging from syntax to access levels to object interaction. It also offers extensive consideration of third-party management interfaces, including tools for metering traffic and predicting traffic growth and behavior. If you're a network operator, network device engineer, or MPLS application developer, you need this book to get all you can out of all of MPLS's many capabilities. * The only book devoted entirely to the tools and techniques for controlling, monitoring, debugging, and optimizing MPLS-enabled networks. * Authoritative information from the co-author of most IETF MIBs relating to MPLS and GMPLS, PWE3, and PPVPN. * Covers both standards-based and proprietary management technologies. * Includes interviews with seminal figures in the development of MPLS. * Via a companion web site, provides information on late-breaking developments in MPLS management and links to additional resources. * To be followed by a second volume presenting best-practice case studies dealing with how real companies approach the management of their MPLS networks.
Includes bibliographical references (p. 499-504) and index.
Keywords: MPLS standard; Computer network protocols; Computer networks -- Management; Electronic books